Response Surface Approach to Optical Channel Dropping Filter Design Parameters Optimization - Hazura, H.; Aliman, F.; Zain, A.S.M.; Hanim, A.R; Salehuddin, F.; Idris, S.K; Nor Syaimaa, M.Z (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
The objective of this paper is to optimise the design parameters for the optical channel dropping filter, which is based on the microring resonator topology. The most important parameters to determine the performance of the microring channel optical filter are the waveguide width, gap, core thickness and ring radius. The determination of parameters by classical experimental design methods requires a large amount of experimental data, which has been found to be costly and time-consuming. To overcome this drawback, a design of experiment (DOE) methods of the Response Surface Methodology (RSM) was employed. This paper employed the RSM design analysis in evaluating the performance of the microring resonator with different design parameters settings. Upon completion, the RSM shows that the optimum condition can be achieved when the ring radius is 5.50μm, a gap of 200nm, waveguide width of 418 nm and core thickness of 220 nm. In conclusion, for optimized performance of the channel dropping filter, design conditions within the range demonstrated in this study are suggested.